PERBANDINGAN SIKAP PENGGUNA DAN BUKAN PENGGUNA SMARTPHONE ANDROID SAMSUNG DI JAKARTA UTARA - M. Fuad, SE., MP; Lily Harjati; Antonio Audy Effendy (Jurnal Ekonomi Perusahaan, 2016)
In daily life, people need communication as one of their basic needs. Following the development of this technology, the new way to communicate starts to grow as well. Smartphone is one of a communication tool to help people in both getting and disseminating the information swiftly. Samsung is a popular smartphone which turns out to be a trend in society, due to its high quality product and useful functions for the customers.This research uses the concept of attitude, which is able to affect one’s mind in choosing a smartphone product on the market with the uniqueness and diversity of each existing brand. Therefore, Samsung as one of the leading smartphone brand is chosen to measure the attitude comparison between users and non-users, especially in the youth communities. The purpose of this research is to determine how well the attitude between those communities.The method used in this research is descriptive method using survey approach. The method for collecting data is based on communication technique by distributing questionnaire. While, the sampling method uses judgement sampling.The result of this analysis based on Samsung smartphone users shows that they have a neutral stance towards Samsung smartphone. On the other hand, according to the non-users side, they show a favorable attitude towards it. Both Samsung smartphone users and non-users have different attitude towards the product. Therefore, Samsung needs to boost its customer loyalty by proving that Samsung product is much better than the other smartphones. In addition, for non-users group, Samsung has to be able to attract them to become potential buyer and increase the sales significantly.